State dependence in access to credit - Pigini, Claudia; Presbitero, Andrea F.; Zazzaro, Alberto (Journal of Financial Stability, 2016)
This paper investigates whether firms’ access to credit is characterized by state dependence. We introduce a first-order Markov model of credit restriction with sample selection that makes it possible to identify state dependence in presence of unobserved heterogeneity. The results, based on a representative sample of Italian firms, show that state dependence in access to credit is a statistically and economically significant phenomenon and that this is more prominent among medium-large firms.